2014
DOI: 10.1007/s00592-014-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon for hypoglycemic episodes in insulin-treated diabetic patients: a systematic review and meta-analysis with a comparison of glucagon with dextrose and of different glucagon formulations

Abstract: These data indicate that ineffectiveness of glucagon is unfrequent, not different from dextrose; in addition, intranasal and injected glucagon are similarly effective. In the case of failure, a second dose can be administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
0
34
0
4
Order By: Relevance
“…This study indicates, once again, that peptides administered IN may exert effects different from those with usual parenteral administration, as with insulin . Aside from interest in the physiology of alternative routes of peptide administration, a meta‐analysis showed that IN and IM glucagon are similarly effective …”
Section: Glucagonmentioning
confidence: 73%
See 4 more Smart Citations
“…This study indicates, once again, that peptides administered IN may exert effects different from those with usual parenteral administration, as with insulin . Aside from interest in the physiology of alternative routes of peptide administration, a meta‐analysis showed that IN and IM glucagon are similarly effective …”
Section: Glucagonmentioning
confidence: 73%
“…With the acquisition of the product by Eli‐Lilly in 2015, he no longer had contacts of any kind with pharmaceutical companies involved in intranasal glucagon. He received an unrestricted grant from Locemia Solutions ULC for preparation of the meta‐analysis referenced in the text . V. C. declares no conflict of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations